The effectiveness of phosphorus corn plants’ nutrition with Polymixobacterin - Tokmakova, L. M.; Trepach , A. O.; Shevchenko, L. A. (Scientific Progress & Innovations, 2019)
The purpose of the article is to investigate the influence of various methods of using the Polymixobacterin microbial preparation on the phosphorous nutrition of corn plants and to substantiate the effectiveness of the new agricultural practice. Methods of research. Field method, biochemical (determining phosphorus content in grain and leaf-stem part of plants) and agrochemical (determining grain and by-products’ phosphorus yield) and statistical methods were used during the study. The research results. According to the results of the conducted researches, it was established that on the average over the three years of investigations the tendency of increasing phosphorus content in corn grain of experimental variants with the application of a microbial preparation up to 0.50–0.55 % was revealed in comparison with the control variant, in which this index was 0.47 %. Conducting the surface treatment of vegetating plants in the 7–9 leaf phase on the background of bacterization increased the total phosphorus removal in grain harvest by 53.2 %, and in by-product – by 36.3 %. The elements of scientific novelty. The peculiarities of the impact of the new method of applying Polymixobacterin, which includes the bacterization of seeds and surface treatment of vegetating plants, on the intensity of phosphorus nutrition of corn and removing this element with the yield were revealed. Practical significance. Based on the experimental studies it was established that at cultivating corn, it is expedient to use of agricultural practices, which include seed bacterization and surface treatment of vegetating plants with Polymixobacterin, which affects the enhanced phosphorus assimilation by plants and contributes to increasing its content in leaf-stalk mass and corn grains, and as a consequence, the removal of this element in the crop yield is raised, which testifies to growing the effectiveness of phosphorous nutrition of corn plants.